With reverence, actions have bounds: the relationship between awe and junior high school students’ self-control—the mediating role of meaning in life - Zhang, Yuhan (Frontiers in Psychology, 2026)
IntroductionSchool bullying is frequent among Chinese junior high school students, and this phenomenon is associated with insufficient reverence and poor self-regulation, making awe education an urgent need. Based on the self-control strength model, prototype model of awe, and hierarchical model of meaning, this study aimed to explore the relationship between awe (including trait and state awe) and self-control among junior high school students, with meaning in life as the mediating variable.MethodsTwo complementary studies were conducted. Study 1 adopted a cross-sectional survey design, administering the Chinese Trait Awe Vocabulary Rating Questionnaire, Self-Control Scale, and Meaning in Life Scale to 476 junior high school students. Study 2 used an experimental design, in which positive and negative state awe were primed among 239 junior high school students to examine causal relationships.ResultsThe results revealed two key findings: (1) Meaning in life fully mediated the relationship between trait awe and self-control; (2) Meaning in life partially mediated the relationship between positive-state awe and self-control. Negative-state awe showed no significant mediating pathway with self-control through meaning in life.DiscussionConsistent with theoretical expectations—where awe enriches meaning in life via schema accommodation and meaning in life enhances self-control by promoting long-term goal pursuit—these findings confirm that awe influences junior high school students’ self-control through the mediating role of meaning in life. This study provides empirical support for the theoretical link between awe and self-regulation, and offers practical insights for designing awe education programs to enhance adolescents’ self-control and reduce school bullying.